Preliminary discussion on the potential of zakat-waqaf collaboration in the provision of housing for the needy Muslims - Abdul Rashid, Khairuddin; Hasan, Sharina Farihah; Ahmad Sarkawi, Azila; Othman, Jamilah; Aripin, Srazali (2015)
Zakat and waqaf are the two key instruments that focus on providing assistance to the needy. While they share similar aim but their approaches are different. Zakat has specific approach as prescribed in Al-Quran and Al-Hadiths whereas waqaf in general has no direct Quranic injunction except the various verses and hadiths that promote the practice of infaq. It is a known fact that within the Malaysian context, the employment of these two instruments have been relatively successful in fulfilling their respective roles and functions. However, few research have been done on the potential of these two instruments collaborating in specific endeavours for the benefit of the muslim ummah. Through desk study and discussions with experts, this paper explores the potential of zakat and waqaf to collaborate - in terms of their resources and within what is permissible under the shari’ah. The focus of this paper is on the collaboration between zakat and waqaf resources in the provision of low cost housing or its equivalent for needy muslims. The paper concludes with several issues and challenges that would require further and in-depth deliberations. Keywords: economy, poverty, housing, waqaf, zakat